Residual stress analysis in cold-worked holes with interference bushing. (10th April 2007) - Giglio, Marco; Lodi, Marco
Cold working is widely applied in fatigue design of mechanical and aeronautical components with holes in order to induce a stress compression field in the most loaded zone and thus increase fatigue life. None of the investigations in literature consider the insertion of a bushing in the hole by a cold expansion process: in particular cases may be predicted the presence of tensile circumferential residual stress on hole surface, often loaded by external cyclic forces. The present investigation introduces a closed-form analytical method for simply predict the complete residual stress distribution on a cold-expanded bushing-hole connection commonly used in aerospace structures, under imposed conditions. A comparison of these solutions with 2-D finite element analysis reveals perfect agreement. Finally, the paper discusses the results of the closed-form solution obtained on several bushing-hole combinations, providing interesting indications in the fatigue design in order to obtaining the highest benefits on hole fatigue life.